Gamification as an engagement tool in e-Learning websites - Rebelo, Sofia (2020)
Aim/Purpose As e-Learning becomes increasingly pervasive, students’ engagement in online settings emerges as a central challenge, as it is often more demanding to ensure in this context. The core importance of engagement for e-Learning, places a focus on various instruments and strategies that can be deployed to foster its enhancement. Background Gamification is often depicted as a significant instrument to drive engagement, behavior change, and loyalty, which can be of great significance to online learning. This paper aims to examine the relationship between the application of gamification tools and the level of engagement in e-Learning websites. Methodology This research used two methods: the analysis of e-Learning websites and an online survey with a convenience and purposive sample of e-Learning and/or gamification experts. Contribution This paper adds to the existing body of research by placing and emphasis on and examining the positive role of gamification as an engagement instrument with valuable potential for e-Learning. Findings The results showed that the majority of the selected e-Learning websites use gamification and engagement elements and that the tools that are more commonly used were deemed as the most effective, by the experts. It became equally evident that the deployment of a larger number of gamification and engagement elements have positive repercussions in the enhancement of engagement, which can have constructive ramifications for the effectiveness of e-Learning. Recommendations for Practitioners From a practitioner’s viewpoint the findings can assist both learning designers and teachers in the creation of gamification strategies to enhance students’ engagement. As a central challenge of e-Learning courses, engagement requires a multifaceted approach to be addressed effectively and knowing the strategies that have positive outcomes is a step forward in ensuring that the students can enroll in online courses and not be compromised with respect to their engagement. Finally, the lack of engagement can have serious repercussions not only on the learning experience of the students, but also on their actual academic performance. Hence, it is important to guide educators towards good design practices that can maximize engagement in these settings. Recommendation for Researchers From a research perspective, these findings add to a growing body of studies that focus on the benefits of gamification by highlighting its positive repercussions on engagement and identifying which elements are more effective. In addition, the use of different sources of data provided a wider illustration of what is currently the use of gamification elements by functioning e-Learning websites and how those who apply them in practice in their courses perceive these elements. Future Research Future research endeavours can focus on exploring students’ perceptions of gamification and how it influences their leaning performance.